LEGAL PROBLEMS OF EDUCATION EQUALITY IN REMOTE AREAS - Nancy Prema (NOMOI Law Review, 2023)
Indonesia is the country that has the most population in the world, this is certainly inseparable from all legal problems in society. The existence of government prosecutions of the public to understand the law (presumption iures de iure) is certainly compared to limited education, material limitations, the unevenness of development or education services, and regional remoteness. This journal aims to provide an explanation regarding why all Indonesians are required to understand the law while the government has not met the needs/services in the community in an effort to achieve a state based on law. The research steps taken use qualitative methods where the contents of this journal contain data and the results of direct observations. Based on the results of direct research into the community that there are still many Indonesian citizens who do not understand the law due to limited education due to the remoteness of the area.